Cytochrome P4501A Induction by Highly Purified Hexachlorobenzene in Primary Cultures of Avian Hepatocytes - Mundy, Lukas (Université d'Ottawa / University of Ottawa, 2011)
Hexachlorobenzene (HCB) is a persistent organic pollutant that was primarily produced for use as a fungicide dating back to the 1940s. Worldwide emissions have declined steadily over the past forty years, but HCB is still produced as a by-product of a number of industrial processes and is still detected in remote locations around the globe. Many studies have been conducted to determine the toxic and biochemical effects of HCB, but it has been suggested that reported toxic and biochemical effects initially attributed to HCB exposure may have actually been elicited by contamination of HCB by polychlororinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs) and dioxin-like polychlorinated biphenyls (PCBs). This thesis investigates whether highly purified HCB (HCB-P; defined as HCB containing < 0.2 ppb of any PCDD, PCDF, or co-planar PCB congener [the detection limit of current analytical methods]) can induce cytochrome P4501A (CYP1A) in three avian species in vitro. Primary cultures of chicken (Gallus gallus domesticus), ring-necked pheasant (Phasianus colchicus) and Japanese quail (Corturnix japonica) embryo hepatocytes were used to compare the potencies of reagent-grade (RG-HCB), HCB-P and 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) as inducers of ethoxyresorufin O-deethylase (EROD) activity, CYP1A4 messenger ribonucleic acid (mRNA) and CYP1A5 mRNA. The potencies of two mono-ortho substituted PCBs, 2,3,3’,4,4’-pentachlorobiphenyl (PCB 105) and 2,3’,4,4’,5-pentachlorobiphenyl (PCB 118) were also assessed in chicken embryo hepatocytes using the same endpoints. All compounds induced EROD activity and up-regulated CYP1A4/5 mRNAs in the hepatocytes of each species. The potency of HCB relative to the potency of TCDD (ReP) was 0.0001, 0.001 and 0.01 in chicken, ring-necked pheasant and Japanese quail embryo hepatocytes, respectively. ECthreshold values were suggested to be more appropriate than EC50 values because ECthreshold values account for differences in maximal EROD and CYP1A4/5 mRNA levels that are observed with HCB exposure in avian embryo hepatocytes more so than EC50 values. Differences in species sensitivity to HCB were also assessed, and did not vary as greatly as the listed ReP values. The results presented herein suggest that HCB is capable of inducing effects downstream of activation of the aryl hydrocarbon receptor, and may warrant its inclusion in the World Health Organization’s toxic equivalency concept.
Keywords: Hexachlorobenzene; organic pollutants; fungicide; HCB